Age and Hydration of Competing Horses Influence the Outcome of Elite 160 km Endurance Rides - Bollinger, Lena; Bartel, Alexander; Küper, Alina; Weber, Corinna; Gehlen, Heidrun (Frontiers in Veterinary Science, 2021)
High elimination rates and the concern for horse welfare are important issues in endurance riding. An improved understanding of the causes of elimination could increase completion rates in this sport. We have identified pre-ride risk factors that allow an assessment of potential elimination before the ride. A longitudinal cohort study was performed among 49 healthy horses competing in the 160 km endurance ride at the 2016 World Championship of Endurance Riding in Samorin/Slovakia. Blood samples were drawn before the ride. For statistical evaluation, horses were categorized in three groups: finishers, lame and metabolically eliminated horses. Risk factors were calculated for each group using multinomial logistic regression. A 1% increase in hematocrit levels was associated with a higher OR for elimination (lameness: OR 1.26, p = 0.017; metabolic: OR 1.34, p = 0.010). Furthermore, increased potassium values correlated negatively with the race outcome. For a 1 mmol/l increase in potassium, the lameness OR was 4.21, p = 0.039 and metabolic OR was 1.15, p = 0.848. Eight-year-old horses had a 100% elimination rate and survival analyses showed a significantly higher hazard for elimination (p = 0.025). We thus conclude that age and hydration affect the outcome of elite endurance rides. Further investigation of age as a risk factor seems to be clinically relevant and adjustments of FEI qualification modes may be appropriate.